FORM AND CONTEMPORARY SCENARIO OF AIPAN, THE FOLK ART OF UTTARAKHAND - Kumar, Ravi; Singh, Gurcharan (International Journal of Research -GRANTHAALAYAH, 2026)
folk arts of Uttarakhand are a symbol of ancient and rich traditions. On auspicious occasions like festivals, weddings, naming ceremonies, etc., people here plaster their homes and courtyards with ochre and create beautiful patterns called ’Aipan’ using rice powder. Women create these patterns with their fingers and reflect religious and cultural symbols. Slight variations in the style of Aipan are found across different sections of society – for example, the Brahmin community uses white Biswar, while the Sah community creates Aipan using a combination of yellow color and drops. Apart from this, clay idols (Dikara) and Chowkis, Peethas, Pattas etc. are also made on traditional occasions, which are a living example of the folk creativity of Uttarakhand. Phuleria (2022), At present, it is not only limited to folk rituals, but is also making its strong presence felt in the fields of design, clothing, home decoration, tourism and business. This research paper presents an analysis of the traditional form, social significance, craft techniques and its contemporary adaptation of Aipan art.